IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENDORONG INOVASI PROGRAM ALUMNI KUNJUNG DAN ORANG TUA MENGAJAR DI SMK NEGERI 3 PALANGKA RAYA - Azarya Apri; Evi Mariani; Joni Saputra (Jurnal Manajemen Pendidikan, 2026)
The study aims to describe the planning, implementation, and evaluation of school-based management in fostering the "Alumni Visits" and "Parents Teaching" programs at SMK Negeri 3 Palangka Raya. A qualitative approach using a phenomenological design was employed. Data sources comprised primary and secondary data collected through interviews and document analysis. The research stages included pre-fieldwork (designing the study and preparing instruments), data collection, analysis, and reporting. Data analysis involved collection, reduction, presentation, and conclusion drawing. The results indicate that: (1) program planning was conducted in a structured manner through needs analysis and meetings involving both internal and external stakeholders; (2) program implementation was managed by the curriculum division through targeted communication and coordination among the school, alumni, and parents, although the school had not yet provided guidance on material delivery strategies or instructional media for the parents; and (3) evaluation was implemented for the "Alumni Visits" program based on school-set objectives—such as increasing entrepreneurial motivation—whereas the "Parents Teaching" program had not been evaluated due to the absence of specific indicators or intended goals.